2005
DOI: 10.1039/b503358f
|View full text |Cite
|
Sign up to set email alerts
|

Nafion-stabilized magnetic nanoparticles (Fe3O4) for [Ru(bpy)3]2+(bpy = bipyridine) electrogenerated chemiluminescence sensor

Abstract: A highly sensitive and stable [Ru(bpy)3]2+ ECL sensor has been fabricated based on the multilayer films of Nafion-stabilized magnetic nanoparticles (Nafion/Fe3O4) formed on a platinum electrode surface by means of an external magnet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…In this work, we have synthesized Fe 3 O 4 nanoparticles in-situ in PFSI solution similar to Kim et al [21] reported. This prestabilization procedure could solve the above mentioned problems successfully, although the interaction mechanism between Fe 3 O 4 and PFSI is unclear and need further investigation.…”
Section: Introductionmentioning
confidence: 79%
“…In this work, we have synthesized Fe 3 O 4 nanoparticles in-situ in PFSI solution similar to Kim et al [21] reported. This prestabilization procedure could solve the above mentioned problems successfully, although the interaction mechanism between Fe 3 O 4 and PFSI is unclear and need further investigation.…”
Section: Introductionmentioning
confidence: 79%
“…Other nanomaterials, such as SiO 2 [54], clay [55], Fe 3 O 4 [56], and Zeolite Y sieves [57], are also used as electrode modification materials to construct functionalized electrode interfaces for ECL biosensors. These materials have a high chemical inertness and provide a wide range of anode working potentials with low electrical resistivity.…”
Section: Nanomaterials As Modification Electrode Materialsmentioning
confidence: 99%
“…The ECL sensor was fabricated based on the multilayer films of Nafion-stabilized magnetic nanoparticles (Nafion/Fe 3 O 4 ) formed on a platinum electrode surface by means of an external magnet. The ECL sensor based on the Nafion/ Fe 3 O 4 multilayer films is more sensitive than that based on pure Nafion films, which is maybe due to the fast mass transport in the Nafion/Fe 3 O 4 multilayer films [56]. …”
Section: Nanomaterials As Modification Electrode Materialsmentioning
confidence: 99%
“…Nanoscale Fe 3 O 4 has been applied in magnetic ink [3] , electronics and bio-sensitive materials [4,5] , high density magnetic recording media and biomedical fields [6][7][8][9] , because of its good compatibility with organism and its electrical and magnetic characteristics of its size and morphology. Therefore, the preparation of Fe 3 O 4 nanostructures and its properties research are extremely active in recent years.…”
Section: Introductionmentioning
confidence: 99%